Decomposition for Decarbonisation: Evaluation of Decarbonisation Programmes. (September 2016) - Harper, Peter
The Kaya Identity has long been used as a simple yet rigorous way to assess options in energy and climate policy. Its shortcoming is that it fails to address the very wide range of non-energy factors. This paper presents a simple extension of the Kaya Identity – the Emissions Quantification Tool or EQT – that incorporates the missing factors while retaining the mathematical transparency of the original. The tool allows national policies to be analysed and compared with international standards for allowable quotas, from which shortfalls or 'carbon debts' can be calculated. It can be used to represent almost any conceivable decarbonisation programme, testing assumptions and revealing necessary rates of change. The paper demonstrates the use of the tool by analysing prevailing UK policy and variant scenarios. The results are often surprising.